Global perspectives on educational testing : examining fairness, high-stakes and policy reform - Arbuthnot, Keena (Bingley, U.K. : Emerald Publishing Limited, 2017)
This book provides a refined definition of standardized educational test fairness that can be utilized in multiple contexts to better understand the experiences and perspectives of diverse groups of test takers. Globally, there has been a significant influx in the use of and dependence on standardized tests to foster educational improvements. Standardized testing programs such as TIMSS (Trends in International Mathematics and Science Study), are designed to provide information about a country's global standing in multiple academic areas, ranking individuals and/or groups relative to the performance of others. The high-stakes nature of standardized tests has increased public concern and interest in issues related to test fairness. Since standardized test performance has a profound influence on multiple aspects of educational systems, it is imperative to better understand and examine issues of fairness.
Includes index.
Includes bibliographical references.
Keywords: Educational tests and measurements -- Evaluation; Fairness; Multicultural education